Memória: Práticas Sociais, Culturais e Educacionais de Mulheres Louceiras em Cajazeiras - Paraíba. - Silva, Maria do Socorro Soares Costa e (2010)
This dissertative paper has as main goal to investigate, from the memory of female chinaware makers, how the social, cultural and educational practices have occurred or still do for the construction of the identity of the meanings of the woman being, in the Chinaware Makers Association, in the neighborhood São José in the city Cajazeiras PB. It intends, with this, to offer a contribution to the current studies of memory, culture and gender in the history of the Brazilian Education. This paper is based upon the presupposes of the New Cultural History, specifically in the interrelation between non-formal education, cultural practices and gender. It is also based upon the oral History, supported by the memory field, theoretical basis which give support to the understanding as to how the subjects reconstitute, by the quotidian history, the different ways of living the familiar, educative, occupational, leisure and sexual, among other habitual activities. Its main research source is the oral narratives, obtained through recorded interviews and transcribed with the finality of the oral document production. The subjects of this investigative paper are three representative characters of three generations of female chinaware makers of the same family, who have acted as recorders and contributors, being: a young lady (26), an adult (50) and an elderly (63). The categories: family, education, profession, moral and ethical principles and the meanings of the woman being have guided the analytical process. On this direction, the analysis of the interviews have showed that the social, cultural and educational practices of the female chinaware makers happened and still do in the identity construction continuous process of the meanings do the woman being by the function occupied by each individual, specifically, the concrete way of life of each woman, by the representations inscribed in these practices, such representations which move the relations men/women and give light to the ideas and to the concepts of cultural diversity to which all the country permeates.